1995
DOI: 10.1002/ptr.2650090205
|View full text |Cite
|
Sign up to set email alerts
|

Effects on blood pressure of caffeic acid analogues isolated from Salviae Miltiorrhizae Radix in rats with adenine‐induced renal hypertension

Abstract: The effects of caffeic acid analogues isolated from Salviae Miltiorrhizae Radix were examined in rats with adenine-induced renal failure and hypertension. Systolic, mean and diastolic blood pressures were decreased after magnesium lithospermate B administration. Oral administration of lithospermic acid B also decreased these blood pressure values even though the effects were weaker than those of magnesium lithospermate B. However, rats given lithospermic acid, rosmarinic acid or caffeic acid showed no apprecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…We hypothesized that the improved kidney function in MLB-treated mice was related (at least in part) to the enriched Odoribacter genus via a cardiovascular pathway [37]. We did not monitor blood pressure during our study, but MLB's antihypertensive effect has been reported [40,41]. Our study observed, for the first time, a potential connection between MLB's antihypertensive effect and the gut microbiota.…”
Section: Discussionmentioning
confidence: 86%
“…We hypothesized that the improved kidney function in MLB-treated mice was related (at least in part) to the enriched Odoribacter genus via a cardiovascular pathway [37]. We did not monitor blood pressure during our study, but MLB's antihypertensive effect has been reported [40,41]. Our study observed, for the first time, a potential connection between MLB's antihypertensive effect and the gut microbiota.…”
Section: Discussionmentioning
confidence: 86%
“…72 Plantderived caffeic acid analogues fed to rats with adenine-induced renal hypertension were able to lower systolic blood pressure. 73 Grape polyphenolics administered to rats reduced thrombin-induced platelet aggregation 74 and grape juice inhibited platelet activity and thrombosis in stenosed canine coronary arteries. 75 Phenolic acids, such as caffeic acid, have been shown to protect cultured endothelial cells against the cytotoxic effects of oxLDL, possibly by blocking the intracellular signalling triggered by oxLDL.…”
Section: Other Biological Activitymentioning
confidence: 99%
“…13,14) Different studies have shown that Sal B has a variety of biological activities including anti-oxidation, 15,16) antifibrotic, 17) and myocardial salvage effects 18) ; it also prevents hepatitis and uremia, 19) and improves blood circulation and renal function. [20][21][22][23][24][25] Considering their prominent pharmacological activities and high content in Danshen, both TSIIA and Sal B have been selected as marker components for the quality control of Danshen and many other medicinal preparations containing Danshen in the 2005 edition of Chinese Pharmacopoeia. 6,12,26) The chemical structures of TanIIA and Sal B are shown in Fig.…”
mentioning
confidence: 99%